2010
DOI: 10.1246/cl.2011.28
|View full text |Cite
|
Sign up to set email alerts
|

Helicity Induction and Memory of Syndiotactic Poly(methyl methacrylate) Assisted by Optically Active Additives and Solvents and Chiral Amplification of Helicity

Abstract: Syndiotactic poly(methyl methacrylate) (st-PMMA) was found to fold into a preferred-handed helix with amplification of helicity assisted by chiral additives and solvents and further encapsulated fullerenes within its helical cavity whose helicity was memorized after removal of the chiral molecules.Syndiotactic poly(methyl methacrylate) (st-PMMA), a stereoregular commodity polymer, forms a thermoreversible gel in aromatic solvents, such as toluene and chlorobenzene, in which the st-PMMA possesses a 74/4 helical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 13 publications
2
26
0
Order By: Relevance
“…It shows a strong bisignate signal at 1191 and 1168 cm –1 , corresponding to the out-of-phase antisymmetric stretching mode of the C–O–C group near the polymer main chain and twisting mode of the CH 2 group on the main chain, and a very weak negative peak at 1144 cm –1 belonging to out-of-phase antisymmetric stretching of C–O–C near the main chain and rocking of CH 2 on the main chain. These peaks in the VCD spectrum are consistent with those of syndiotactic poly­(methyl methacrylate) (PMMA) reported previously. , By comparison of the VCD spectra of PIPEMA 36 and optically active syndiotactic PMMA induced by chiral aromatic alcohol (( R )- or ( S )-1-phenylethanol), it is suggested that the PIPEMA has a left-handed helical conformation, which should be the origin of chirality in the present system. Consequently, the chirality of the PIPEMA was transferred to the chiral assemblies of GNRs, producing strong chiroptical signals in their LSPR range.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It shows a strong bisignate signal at 1191 and 1168 cm –1 , corresponding to the out-of-phase antisymmetric stretching mode of the C–O–C group near the polymer main chain and twisting mode of the CH 2 group on the main chain, and a very weak negative peak at 1144 cm –1 belonging to out-of-phase antisymmetric stretching of C–O–C near the main chain and rocking of CH 2 on the main chain. These peaks in the VCD spectrum are consistent with those of syndiotactic poly­(methyl methacrylate) (PMMA) reported previously. , By comparison of the VCD spectra of PIPEMA 36 and optically active syndiotactic PMMA induced by chiral aromatic alcohol (( R )- or ( S )-1-phenylethanol), it is suggested that the PIPEMA has a left-handed helical conformation, which should be the origin of chirality in the present system. Consequently, the chirality of the PIPEMA was transferred to the chiral assemblies of GNRs, producing strong chiroptical signals in their LSPR range.…”
Section: Resultssupporting
confidence: 91%
“…These peaks in the VCD spectrum are consistent with those of syndiotactic poly(methyl methacrylate) (PMMA) reported previously. 61,62 By comparison of the VCD spectra of PIPEMA 36 and optically active syndiotactic PMMA induced by chiral aromatic alcohol ((R)-or (S)-1-phenylethanol), it is suggested that the PIPEMA has a left-handed helical conformation, 62 which should be the origin of chirality in the present system. Consequently, the chirality of the PIPEMA was transferred to the chiral assemblies of GNRs, producing strong chiroptical signals in their LSPR range.…”
Section: Resultsmentioning
confidence: 80%
“…Previously, we found that syndiotactic poly(methyl methacrylate) (st‐PMMA), a commodity plastic, folds into a preferred‐handed helical conformation (18 1 ‐helix) with an inner cavity of approximately 1 nm in toluene in the presence of an optically active alcohol or amine, accompanied by gelation, in which a series of achiral (C 60 and C 70 ) and chiral fullerenes (e.g., C 76 , C 78 , C 80 , C 90 , and C 96 ) are size‐ and enantio‐selectively encapsulated within its helical cavity through an induced‐fit mechanism to form optically active peapod‐like inclusion complexes which are retained after removal of the chiral additives (helicity memory) . We also found that a preferred‐handed helical st‐PMMA can serve as an optically active polymeric host to encapsulate the complementary isotactic PMMA (it‐PMMA) in a helix‐sense‐controlled manner to produce the first optically active PMMA stereocomplex …”
Section: Figurementioning
confidence: 99%
“…3 Inspired by the sophisticated functions of naturally occurring optically active polymers, such as proteins, DNA and sugars, current research on nanoscale control over chirality of polymers and supramolecules, together with a molecular design, is being undertaken with the goal of developing novel optically active functional materials. Recent examples include polymethacrylates, 5 polyacetylenes, 6 polyamides, 7 oligo peptides, 8 amidine oligomers, 9 polyallenes, 10 polyisocyanides, 11 polyphosphazenes, 12 supramolecular assemblies of trisubstituted benzenes 13 and π-conjugated molecules. Chirality amplification is often observed in helically twisted synthetic polymers and supramolecular polymers obtained by the copolymerization of enantiomeric monomers and chiral/achiral monomers.…”
Section: Introductionmentioning
confidence: 99%
“…Chirality amplification is often observed in helically twisted synthetic polymers and supramolecular polymers obtained by the copolymerization of enantiomeric monomers and chiral/achiral monomers. Recent examples include polymethacrylates, 5 polyacetylenes, 6 polyamides, 7 oligo peptides, 8 amidine oligomers, 9 polyallenes, 10 polyisocyanides, 11 polyphosphazenes, 12 supramolecular assemblies of trisubstituted benzenes 13 and π-conjugated molecules. 14 Green et al have proposed "majority rules" and "sergeants and soldiers" principles regarding chirality amplification in synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%